Preventive effects of betamethasone valerate ointment for radiation-induced severe oral mucositis in patients with oral or oropharyngeal cancer: protocol for a multicentre, phase II, randomised controlled trial (Bet-ROM study). Issue 1 (17th January 2022) - Soutome, Sakiko; Otsuru, Mitsunobu; Murata, Maho; Kawashita, Yumiko; Yoshimatsu, Masako; Funahara, Madoka; Yamamura, Yoshiko; Hasegawa, Takumi; Yamada, Shin-ichi; Kojima, Yuka; Nakahara, Hirokazu; Shibuya, Yasuyuki; et al.
Abstract : Introduction: This is a randomised, multi-centre, open-label, phase II study to evaluate the efficacy of betamethasone valerate ointment on radiation-induced oral mucositis in patients with head and neck cancer undergoing concomitant radiotherapy with cisplatin or cetuximab. Methods and analysis: The trial will take place at seven hospitals in Japan. Patients will be randomised (1:1) into betamethasone and control groups after the occurrence of grade 1 oral mucositis. In the betamethasone group, patients will use betamethasone valerate ointment five times a day, in addition to usual oral hygiene guidance. The primary endpoint is the incidence and onset time of grade 3 oral mucositis. The secondary endpoints are the incidence and onset time of grade 2 oral mucositis, incidence and onset time of oral candidiasis, completion of radiation therapy and adverse events. Target accrual is 102 patients with a two-sided type I error rate of 5% and 80% power to detect an 80% risk reduction in the incidence of grade 3 oral mucositis. Ethics and dissemination: This study was approved by the Clinical Research Review Board of Nagasaki University (No. CRB20-009). All participants will be required to provide written informed consent. Findings will be disseminated through scientific and professional conferences and peer-reviewed journal publication. The datasets generated during the study will be available from the corresponding author on reasonable request. Trial registration number: jRCTs071200013.